Pendekatan Keadilan Gender Pada Penerapan Iddah Ditinjau Dari Studi Islam - Riha Nadhifah Minnuril Jannah; Naning Faiqoh (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2021)
This paper aims to discuss the concept of iddah which is considered to discriminate against women because it is considered to limit women's movement after divorce or death by their husbands. But in that case Islam actually has clearly regulated in the Qur'an and hadith. Therefore, the problem that wants to be researched and analyzed is how the application of iddah today in Islamis gender equitable and is still relevant if applied. From the research results, there is actually no more injustice of any kind against women, let alone using religious legitimacy to discredit women. Because basically Islam is earlier than the history of any religion which pays special attention to the dehumanization of humanity experienced by women and serves which function as Khalifah fi al-ard. And iddah is still very relevant if it is applied today because in fact, even though today there are many discoveries and modern sciences that undermine the aims of iddah and assume that there is discrimination against women, infact there are many lessons and goals that can be taken from the process of having iddah.